Um olhar sobre o mal-estar docente na perspectiva da contemporaneidade - Gregorin, Cristiane Pinholi (2016)
The present research has as subject and object of study "The teacher malaise in contemporary society." To problematize it that characterizes the teaching malaise and how it develops in the school environment.Hypotheses presents the teacher malaise is manifested by a sense of guilt, teacher accountability on the numerous conflicts that human relations in teaching impose; the teacher who feels this malaise is weakened in relation to their peers and other subjects in the school environment and the teaching malaise does not arise suddenly, on the contrary, it appears gradually, a shy way, and when they realize it is already bringing negative consequences to the teacher and his work.The study has the objective to understand the teacher malaise in the context of internal relationships to school to think about strategies aimed at overcoming the problem and specific objectives: research the characteristics of teacher malaise; analyze the influence of the contradictions of society and contemporary culture in teacher malaise and identify how interpersonal relationships with students and other subjects at school collaborate to this teacher malaise. The theoretical research is based predominantly on research that help to understand the teacher malaise and the Critical Theory of the Frankfurt School. The subjects of empirical research are teachers aged over 30 years, that have some time and experience, they never had in their records, sick leave for signs recognized as teacher malaise, but invited to participate recognize suffer the problem to some degree. Regarding the empirical research methodology, it is of qualitative nature and involves reports of oral histories of thematic subjects' lives, which is possible to extract the following categories of analysis: frustration, discouragement, expectations, coping mechanisms, family and authority. The results were found narratives with high emotional charge, with a wealth of details that made the moment of enabling interviews to self¬reflection and awareness of self and other.It is concluded that the presented objectives have been achieved and that the assumptions listed, partially validated because only referred to the fact that teachers malaise settle slowly was observed in the narratives. On the other hand, there has been a teacher of trouble to relate satisfactorily with the families of students and vise versa, which makes it necessary and central conceptual link between the categories' family and authority "to the understanding of teacher malaise. Anyway, the narrators are unanimous in affirming that human relationships are difficult and, therefore, in this sense ¬ as a possible intervention ¬ can think about what kind of study can be inserted in its basic and continuing education. It is believed that management strategies of people allied to selfknowledge techniques, focusing on the revision of beliefs and values, could help the teacher in his self¬education process, as well as communication campaigns to collaborate for the recovery of the teacher image in society. On the information obtained from this research, there emerges a question for future research: if the family has lost its authority, their children in school ¬ as students ¬ can recognize the teacher an authority that does not see in their parents or guardians?